Prevalência de aneurismas do ventrículo esquerdo em pacientes chagásicos crônicos de duas áreas do Estado do Piauí Prevalence of left ventricular aneurysms among chronic Chagas disease patients from two areas in the State of Piauí, Brazil - José Borges-Pereira; Sérgio Salles Xavier; Andréa Silvestre de Sousa; José Adail Fonseca de Castro; Patrícia Lago Zauza; José Rodrigues Coura (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
Para avaliar a prevalência de aneurismas do ventrículo esquerdo, realizou-se um estudo transversal envolvendo uma coorte de 261 pacientes chagásicos crônicos (156 do município de João Costa e 105 de São do João do Piauí; 146 mulheres e 115 homens com idade média de 57,9 ± 14,2 anos). A avaliação cardiológica foi realizada por exame clínico, eletrocardiograma de repouso e ecocardiograma uni e bidimensional. Foram diagnosticados 23 (8,8%) aneurismas do ventrículo esquerdo: 17 (6,5%) no ápice, quatro (1,5%) na parede posterior, um (0,4%) na parede inferior e um (0,4%) no septo interventricular. Cinco (1,9%) pacientes de São João do Piauí apresentaram trombos associados com aneurismas apicais. A prevalência de aneurismas do ventrículo esquerdo foi maior entre os pacientes de São João do Piauí (13,3%) e entre os homens (13,9%), com diferença não significativa em função da faixa etária. Esses resultados revelam baixa prevalência de aneurismas do ventrículo esquerdo entre os pacientes de João Costa e elevada concentração de trombos entre os pacientes de São João do Piauí. A cross-sectional study involving a cohort of 261 chronic Chagas disease patients (156 from the municipality of João Costa and 105 from São João do Piauí; 146 women and 115 men with mean age of 57.9 ± 14.2 years) was carried out to evaluate the prevalence of left ventricle aneurysms. The cardiological evaluation was performed by means of clinical examination, resting electrocardiograms and one and two-dimensional echocardiograms. A total of 23 cases of left ventricle aneurysms (8.8%) were diagnosed: 17 (6.5%) in the apical segment, four (1.5%) in the posterior wall, one (0.4%) in the inferior wall and one (0.4%) in the interventricular septum. Five patients (1.9%) from São João do Piauí presented thrombi associated with apical aneurysms. The prevalence of left ventricle aneurysms was greater among the patients from São João do Piauí (13.3%) and among men (13.9%), with no significant difference in relation to age group. These results show that there was low prevalence of left ventricle aneurysms among patients from João Costa and high concentration of thrombi among patients from São João do Piauí.